ASPECTS OF KOREAN LITERATURE ACCORDING TO THE STAGE OF ECONOMIC GROWTH: FOCUSED ON THE VIEWS OF AMERICA - KIM, Mansu (International Journal of Korean Humanities and Social Sciences, 2016)
The main topic of this paper is how the economic growth has changed the aspect of Korean novel in the viewpoints of the theory of W. W. Rostow. But the additional topic is Korean's viewpoint on American which had been reflected in Korean novels. Korea has made a long relationship to the United States since 1882. Korea have kept friendly and cooperative relationship to American. But sometimes the relationship was changed rapidly to the opponent or critical attitudes. It should be the universal phenomenon that the people of weak nations begin to have strong nationalistic feelings with the pace of economic growth and gather to show a strong enmity against the strong nation especially against the United States. According to this universal patterns, Korean admired American at first. But after rising to the stage of ‘take-off’, they began to turn to the opponent and critical attitudes. Finally at the age of high mass consumption, they will not compare to America any more because they belong to the similar economic situation. The economy of Japan, Korea and China rose up to higher level at the rapid speed. But the strong nationalistic feelings remained incessantly among their nations. The “European Dream” is one of the attitudes in which individuals find security not through individual accumulation of wealth, but through connectivity and respect for other nations. Our neighbouring countries and Korea must learn the attitudes of European Dream and try to establish this system in East Asia.